Temporal analysis of oxidative effects on the pulmonary inflammatory response in mice exposed to cigarette smoke. - Campos, Keila Karine Duarte (2013)
The most common factor related to the chronic obstructive pulmonary disease (COPD) development is the chronic smoking habit. Our study describes the temporal kinesis of pulmonary cellular influx through BALF analyses of mice acutely exposed to cigarette smoke (CS), the oxidative damage and antioxidative enzyme activities. Thirty-six mice (C57BL/6, 8 weeks old, male) were divided in 6 groups: the control group (CG), exposed to ambient air, and the other 30 mice were exposed to CS. Mice exposed to CS presented, especially after the third day of exposure, different cellular subpopulations in BALF. The oxidative damage was significantly higher in CS exposed groups compared to CG. Our data showed that the evaluated inflammatory cells, observed after three days of CS exposure, indicate that this time point could be relevant to studies focusing on these cellular subpopulation activities and confirm the oxidative stress even in a short term CS exposure.